Criopreservação e desenvolvimento de oócitos bovinos tratados com citocalasina B - Mezzalira, Alceu (2001)
Experiments were conducted to evaluate the effects of cytochalasin B (CB) on the cryopreservation survival rates of bovine oocytes and embryos. In a first study, the embryonic development of in vitro matured bovine oocytes was evaluated, after exposure to different CB doses associated or not to a centrifugation process. In the experiments I and II, four treatments were applied: centrifugation 2100g for 5 minutes (T1); exposure to 7.5μg/mL CB, for 15 minutes (T2); centrifugation after exposure to CB (T3) and oocytes without CB (T4- control). In the experiment III, the oocytes were submitted to three CB concentrations: 7.5μg/mL (T1); 15μg/mL (T2) and 45μg/mL (T3). The cleavage rates (Exp. I), as well as blastocysts and hatching rates (Exp. II) were not influenced by treatments. The exposure to high doses of CB (Exp. III) didn't reduce the cleavage and blastocysts rates. In the subsequent study, the influence of different concentrations of CB was evaluated in the vitrification process of bovine oocytes and embryos produced in vitro. In the experiment I, oocytes were matured for 22 hours, and then vitrified immediately (Vitri treatment) or exposed for 15 to 20 minutes, to a 7.5μg/mL CB solution (CB7.5Vitri treatment) or 45μg/mL (CB45Vitri treatment) prior to vitrification. After 30 seconds of exposure to the equilibrium solution (SV1) and 20 seconds to the vitrification solution (SV2), the oocytes were vitrified in open pulled straws (OPS). The re-warming process was carried out in two steps of 5 minutes each, in solutions with decreasing concentrations of threalose. No differences were observed (P> 0.05) in the cleavage and embryo rates among Vitri, Cito7.5Vitri and Cito45Vitri treatments, which were lower (P <0.05) than the Control. In the Experiment II, expanded blastocysts were allocated in 3 treatments. In the Vitri treatment, the embryos were exposed for 1 minute to SV1 and 20 seconds to SV2 solution, in which the threalose was replaced by TCM-Hepes. In the CB45Vitri treatment, the vitrification was performed after 10 minutes exposure to 45μg/mL CB solution. No difference was observed (P>0.05) in the re-expansion and hatching rates among Vitri and CB45Vitri groups, which were lower (P<0.05) than Control group. The results of this study indicate that the exposure to cytochalasin B had no harmful effect on bovine oocytes during culture and do not show beneficial effects in the vitrification procedure.